If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 3) = -14 + -4x Reorder the terms: -5(3 + x) = -14 + -4x (3 * -5 + x * -5) = -14 + -4x (-15 + -5x) = -14 + -4x Solving -15 + -5x = -14 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -15 + -5x + 4x = -14 + -4x + 4x Combine like terms: -5x + 4x = -1x -15 + -1x = -14 + -4x + 4x Combine like terms: -4x + 4x = 0 -15 + -1x = -14 + 0 -15 + -1x = -14 Add '15' to each side of the equation. -15 + 15 + -1x = -14 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = -14 + 15 -1x = -14 + 15 Combine like terms: -14 + 15 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| R=4x+12 | | 3-(3x-6)=2+5x | | C(m)=0.5m+25 | | 5(2l+7)=55 | | 6z^2+7z+2=0 | | 9(x-2)=-3x+78 | | R=5x-16 | | .5555(9x+12)=10 | | 4-7(1-2v)=-33+8v | | p^2=2p+8 | | -x-2=-12 | | -30-5n=6(n+4) | | -9=117 | | .64x^2-6x-5000=0 | | 3(7X+8)=2(2x-4) | | p+3=80 | | -3x+9=6x+81 | | 3(3m-2)=3(m+3) | | 17x-(3x-6)=34 | | 110=10p | | 4a^5*ab= | | 64knots= | | 2x+x+x-6=36 | | (3w-7)(5w-8)=0 | | 432.94=220+0.78x | | -2-3m=-8 | | -8+21=m-1 | | 18x+14y=65 | | 14x^2y-35x=0 | | -6x+3(-4x+23)=-21 | | d-13=25 | | x-9=-1+7 |